Three-Dimensional Electrospun Poly(Lactide-Co-epsilon-Caprolactone) for Small-Diameter Vascular Grafts - Mun, Cho Hay; Jung, Youngmee; Kim, Sang-Heon; Lee, Sun-Hee; Kim, Hee Chan; Kwon, Il Keun; Kim, Soo Hyun (MARY ANN LIEBERT, INC, 2012)
Nanofibers have been applied to tissue engineering scaffolds because fiber diameters are of the same scale as the physical structure of protein fibrils in the native extracellular matrix. In this study, we utilized cell matrix engineering combined with cell sheet matrix and electrospinning technologies. We studied small-diameter vascular grafts in vitro by seeding smooth muscle cells onto electrospun poly(lactide-co-epsilon-caprolactone) (PLCL) scaffolds, culturing and constructing a three-dimensional network. The vascular grafts constructed using cell matrix engineering were similar to the native vessels in their mechanical properties, such as tensile strength, tensile strain, and e-modulus. Also, they had a self-sealing property more improved than GORE-TEX because PLCL has compatible elasticity. Small-diameter vascular grafts constructed using matrix engineering have the potential to be suitable for vascular grafts.
Keywords: MESENCHYMAL STEM-CELLS; AMERICAN-HEART-ASSOCIATION; MECHANICAL-PROPERTIES; BLOOD-VESSELS; IN-VITRO; SCAFFOLDS; FABRICATION; MANAGEMENT; PROPERTY; DISEASE